Meningkatkan Etika Berbicara Dengan Teman Sebaya Melalui Bimbingan Kelompok Dengan Teknik Modelling pada Siswa SMP - Sumedi Sumedi (Universitas Muria Kudus, 2018)
This study aims to (1) Describe the actions of counselors in using group guidance services with modeling techniques to improve the ethics of talking with peers. (3) Describe the improvement of the ethics of talking with peers by using group guidance services with modeling techniques for students of class IX.B SMP 1 Pancur Rembang Semester II Academic Year 2017/2018. Based on the results of the study the ethics of talking with peers in pre-cycle obtained a score of 130 on average 16.25 percentage 32.25% entered in the category of very poor (SK), cycle I obtained a total score of 533 an average of 22 percentages 44% entered the category less ( K), and in cycle II there was a total score of 939 on average 39 percent 78% in the good category (B). So from the pre-cycle, cycle I, cycle II, the results were 32.25% to 78%, so there was an increase of 45.75%. Based on the results of the discussion it can be concluded that group guidance services with modeling techniques can improve the ethics of talking with peers in class IX.B SMP 1 Pancur Semester II Academic Year 2017/2018